"A Dragon Risen from a Shallow Stream": The South Korean Middle Class Framed Through Narratives of Loss, Progress, and Return. (February 2015) - Heffner, Heather
This article explores the relationship between nationalist narrative and middle-class performativity and how this relationship is challenged by processes of globalization. What types of narrative does the nation-state use to frame the middle class, and how do such representations affect middle-class development? It focuses on the South Korean middle-class post–Korean War, after which the state's claim to legitimacy rested upon creating a large middle stratum to serve as the synecdoche for the nation. This normative middle-class project was increasingly articulated in neoliberal terms. It then identifies three narrative frames the state used to shape the new urban middle class: loss, progress, and return. I then examine the South Korean middle class as a movement that coalesced or fractured through time in relation to the three narrative framings.